Family Conflict Resolution Patterns: A Study of Wet Sesait in North Lombok - Suci Ramadhani Putri; Raden Sumiadi; Sinardi Sinardi (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
This study examines the patterns of family conflict resolution practiced by the Sesait Customary Law Community (Wet Sesait) in North Lombok. Using a legal sociology approach with qualitative methods, this research analyzes the integration between Tau Lokaq Empat (the traditional leadership structure) and the Majelis Krama Desa (MKD) in resolving family conflicts. Tau Lokaq Empat consists of four pillars: Mangku Gumi (traditional/adat leader), Jintaka (socio-economic leader), Penghulu (religious leader), and Pemusungan (governmental leader). The MKD, established under North Lombok Regent Regulation No. 20 of 2017, functions as a formal village institution integrating three legal systems: positive law, customary law, and religious law. Research findings reveal that conflict resolution follows a structured yet flexible procedure involving complaint submission, victim-centered verification, formal meetings integrating all four Tau Lokaq Empat pillars, and participatory mediation that synthesizes positive law, customary, and religious perspectives. The binding force of MKD decisions derives from dual legitimacy: formal legal legitimacy through the regent's regulation and socio-cultural legitimacy through the involvement of Tau Lokaq Empat. This integrative model demonstrates constructive legal pluralism in practice, where different legal systems function as complementary resources that create comprehensive and contextual justice, rather than competing entities. This study contributes to understanding how indigenous communities maintain traditional conflict resolution mechanisms while adapting to formal legal systems, offering important lessons for victim-centered restorative justice approaches